Prognostic significance of T‐cell–inflamed gene expression profile and PD‐L1 expression in patients with esophageal cancer. (24th October 2021) - Steiniche, Torben; Rha, Sun Young; Chung, Hyun Cheol; Georgsen, Jeanette Baehr; Ladekarl, Morten; Nordsmark, Marianne; Jespersen, Marie Louise; Kim, Hyo Song; Kim, Hyunki; Fein, Carly; Tang, Laura H.; Wu, Ting; et al.
Abstract: Purpose: The ability of the T‐cell–inflamed gene expression profile (GEP) to predict clinical outcome in esophageal cancer (EC) is unknown. This retrospective observational study assessed the prognostic value of GEP and programmed death ligand 1 (PD‐L1) expression in patients with EC treated in routine clinical practice. Methods: Tumor samples of 294 patients from three centers in Denmark, South Korea, and the United States, collected between 2005 and 2017, were included. T‐cell–inflamed GEP score was defined as non‐low or low using a cutoff of −1.54. A combined positive score (CPS) ≥10 was defined as PD‐L1 expression positivity. Associations between overall survival (OS) and GEP status and PD‐L1 expression were explored by Cox proportional hazards models adjusting for age, sex, histology, stage, and performance status. Results: Median age was 65 years; 63% of patients had adenocarcinoma (AC) and 37% had squamous cell carcinoma (SCC). Thirty‐six percent of tumors were GEP non‐low, with higher prevalence in AC (46%) than SCC (18%). Twenty‐one percent were PD‐L1–positive: 32% in South Korean samples versus 16% in non‐Asian samples and 26% in SCC versus 18% in AC. GEP scores and PD‐L1 CPS were weakly correlated (Spearman's R  = 0.363). OS was not significantly associated with GEP status (non‐low vs low; adjusted hazard ratio, 0.91 [95% CI, 0.69–1.19]) or PD‐L1 expression status. Conclusion: Neither GEP nor PD‐L1 expression was a prognostic marker in Asian and non‐Asian patients with EC. Abstract : In a cohort of 294 patients with esophageal adenocarcinoma and esophageal squamous cell carcinoma from Denmark, South Korea, and the United States, T‐cell–inflamed gene expression profile (GEP) score (non‐low vs low) and PD‐L1 expression status (CPS ≥10 vs CPS <10) showed no significant association with overall survival. Further research investigating prognostic biomarkers in esophageal cancer to inform patient selection for immunotherapy treatment and improve clinical outcomes remains warranted.